2000
DOI: 10.1007/bf02237198
|View full text |Cite
|
Sign up to set email alerts
|

“Dog ear” formation after double-stapled low anterior resection as a risk factor for anastomotic disruption

Abstract: We conclude that the lateral intersections of double-stapled anastomoses are a structural weak spot and that the currently most often applied double-stapled anastomosis is a less effective type of anastomosis than a complete circular one. Resolving this technical problem might help to reduce the number of anastomotic disruptions after low anterior resections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
63
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(64 citation statements)
references
References 8 publications
0
63
1
Order By: Relevance
“…In addition, complications may occur even when the instruments function normally. Anastomotic failure depends on various parameters, including tissue thickness, collagen content, blood flow, improper selection of staple cartridges, ischemia, and tension [8,14]. The most common problem associated with these anastomoses is leakage [2,13].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, complications may occur even when the instruments function normally. Anastomotic failure depends on various parameters, including tissue thickness, collagen content, blood flow, improper selection of staple cartridges, ischemia, and tension [8,14]. The most common problem associated with these anastomoses is leakage [2,13].…”
Section: Discussionmentioning
confidence: 99%
“…The consequence of the instruments misfiring is an important factor [1], and some complications may occur even when the instruments function normally. Anastomotic failure depends on various parameters including tissue thickness, collagen content, blood flow, improper selection of staple cartridges, ischemia, and tension [4,5,9].…”
Section: Discussionmentioning
confidence: 99%
“…However, several problems persist with these mechanical anastomoses [1,9]. Several reports have shown that the incidence of staple line failure in gastrointestinal surgery is low, between 0.5% and 6% [12,16].…”
mentioning
confidence: 97%
“…Although an experimental study of Julian and Ravitch [38] with the subsequent clinical applications of this procedure demonstrated that the vascularization of the distal extremities of anastomosis was adequate in spite of the crossing between two sutures, recent studies confirm that the creation of the ''dog ears'' represent and important risk factors for the development of leakage [38][39][40]. On this subject, recent modified procedure avoids the creation of areas with high risk of ischemia, leaving out the linear from the circular suture [38][39][40].…”
Section: Journal Of Surgical Oncologymentioning
confidence: 98%
“…On this subject, recent modified procedure avoids the creation of areas with high risk of ischemia, leaving out the linear from the circular suture [38][39][40].…”
Section: Journal Of Surgical Oncologymentioning
confidence: 99%